A potential therapeutic drug for osteoporosis: prospect for osteogenic LncRNAs - Meng, Fanjin; Yu, Yang; Tian, Ye; Deng, Meng; Zheng, Kaiyuan; Guo, Xiaolan; Zeng, Beilei; Li, Jingjia; Qian, Airong; Yin, Chong (Frontiers in Endocrinology, 2023)
LncRNAs play essential roles in multiple physiological processes including bone formation.Investigators have revealed that LncRNAs regulated bone formation through various signaling pathways and miRNAs. However, several problems exist in current researches on osteogenic LncRNAs, including sophisticated techniques, high cost for in vivo experiment, as well as low homology of LncRNAs between animal model and human, which hindered translational medicine research . Moreover, comparing with gene editing, LncRNAs would only lead to inhibition of target genes rather than completely knocking them out. As the studies on osteogenic LncRNA gradually proceding, some of these problems have made osteogenic LncRNA researches turning slumped. This review described some new techniques and innovative ideas to address these problems. Although investigations on osteogenic LncRNAs still have obtacles to overcome, LncRNA will work as a promising therapeutic drug for osteoporosis in the near future.